Implementation of Logic and Set Textbook with Ethnomathematics Content Oriented towards Higher-Order Thinking Skills - Subarinah, Sri; Junaidi, Junaidi; Triutami, Tabita Wahyu; Salsabila, Nilza Humaira (Universitas Muhammadiyah Mataram, 2023)
Higher-order thinking skills are skills that are an important aspect of teaching and learning mathematics. Mathematics and culture have a very close relationship, so the development and application of mathematical concepts in the learning process must be based on situations of daily life or local culture. In 2021, Researchers have developed a textbook of Logic and Set containing ethnomathematics oriented toward higher-order thinking skills. The textbook meets the 'Very Good' category on the validity test after being assessed by five experts. This year, the research focuses on the implementation and evaluation of the textbook in Logic and Set courses. The purpose of this research was to describe the feasibility level of the textbook. ADDIE's design research was used in this development research. The trial subjects in this research were 140 students in the Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Mataram who were taking the Logic and Set courses in the 2021/2022 academic year. Data collection techniques in this research were practicality questionnaires and higher-order thinking skills tests. The results of the data analysis for the practicality assessment of the textbook showed an average score of 81.44, which met the practical classification. Then the average value of the students in the final value of the Logic and Set courses is 81.90. In addition, the percentage of students who achieved a score of 75 was 76% or 106 students. Therefore, it can be concluded that the textbook meets the effective criteria.